Penyusunan Laporan Keuangan dengan Menerapkan Standar Akuntansi Keuangan, Entitas Mikro, Kecil dan Menengah (SAK EMKM) pada UMKM Kedai Kopi Bias Rasa Desa Paya Bakung (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the process of preparing financial reports at the UMKM Kedai Kopi Bias Rasa located in Paya Bakung Village by implementing the Financial Accounting Standards for Micro, Small and Medium Entities (SAK EMKM). The method used in this study is qualitative with a descriptive approach. Data were obtained through various methods, namely observation, interviews and documentation. Data analysis techniques were carried out by collecting transaction evidence, grouping and recording transaction evidence into a general journal, making a general journal recapitulation and preparing financial reports based on SAK EMKM. The results of the study indicate that Kedai Kopi Bias Rasa has not implemented SAK EMKM in its financial records, so that the resulting reports do not reflect accurate financial conditions. With the application of SAK EMKM, this study has succeeded in compiling financial position reports, profit and loss reports, and notes to financial statements with more structure. These findings are expected to be a solution for business owners.